Islamic Influence and Dogon Cultural Synthesis: Redefining Cultural Dynamics in Mali - Kutsenkov, Petr A. (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This study aims to re-evaluate the commonly held perception that Islamization leads to the destruction of traditional African cultural symbols and practices. Focusing on the Dogon people of Mali, the research seeks to understand how Islam interacts with and influences their traditional visual culture. Methodology: This study utilizes a combination of observational and ethnographic methods to analyze visual cultural elements in Dogon Country, including sculptures, door locks, traditional buildings, and Dogon mosques, based on extensive fieldwork conducted from 2015 to 2023. Main Findings: Contrary to the notion that Islam erases indigenous visual culture, the study finds a unique form of interaction between Islam and traditional Dogon visual symbols. The Dogon people have retained their beliefs in “jinna” and continue their ritualistic practices. Notably, the influence of Islam has led to the creation of Dogon mosques, which are new architectural forms that incorporate traditional Dogon decorative motifs associated with idol or fetish worship. Applications of This Study: The findings offer significant insights for cultural preservation efforts in Mali and similar contexts. By demonstrating the capacity for harmonious coexistence of Islamic and traditional cultural elements, this research provides a framework for understanding and preserving the rich cultural heritage of the Dogon people. Novelty/Originality of This Study: This study offers a unique insight into the symbiotic relationship between Islamic and traditional Dogon cultures, challenging the common narrative of cultural erasure and highlighting the possibilities of cultural adaptation and synthesis in Africa.